Haemolytic Uraemic Syndrome - a rare case report of bloody diarrhoea in adults - Radhakrishnan,ST; Ruban,A; Uthayakumar,AK; Cohen,P; Levy,J; Teare,J (BMC Gastroenterology, 2019)
Background: Haemolytic uraemic syndrome is a rarely seen in adults often leading to critical illness.This case highlights how difficult it can be to establish a diagnosis and treat when a patient presentswith bloody diarrhoea.Case Presentation: A 17-year-old Iraqi man presented to the emergency department with abdominalpain and bloody diarrhoea. He was initially treated as acute appendicitis, undergoing anappendectomy but following a recurrence in his symptoms a colonoscopy was performed. Adiagnosis of shiga toxin-producing Escherichia coli leading to HUS was suspected following histologyobtained at colonoscopy and this was confirmed on antibody testing. Despite intravenous fluids andsupportive therapy the patient's symptoms and condition deteriorated. He developed seizures andacute renal failure requiring intubation and plasma exchange in the intensive care setting. Heeventually required treatment with ecluzimab therapy; a monoclonal antibody and subsequentlymade a full recovery.Conclusions: Haemolytic uraemic syndrome is a triad of progressive renal failure, thrombocytopeniaand haemolytic anaemia which is a condition rarely seen in adults. It is usually associated with an E.coli infection and supportive therapy remains the mainstay of treatment.